Domestic spaces as crucibles of Paleolithic culture: An archaeological perspective. Issue 172 (November 2022) - Clark, Amy E.; Ranlett, Sarah; Stiner, Mary C.
Abstract: The places in which people live, sleep, prepare food, and undertake other activities—known variably as homes, residential sites, living sites, and domestic spaces—play a key role in the emergence and evolution of modern human culture. The dynamic influence of domestic spaces began early in human evolutionary history, during the Paleolithic/Stone Age. Drawing on examples from Africa and western Eurasia, this article explores aspects of the changing social and cultural significance of domestic spaces throughout this time using several lines of evidence: repeated site visitation, behavioral structuring of living spaces, and information gained by dissecting palimpsest records. With the development of pyrotechnology, living sites become hearth-centered domestic spaces that provided a common hub for activities. Through time the activities around hearths increased in their complexity and diversity. The parsing of palimpsest records by archaeologists also reveals changes in the nature, variety, and intensity of on-site activities through time, indicating shifts in site function and the spatial expression of cultural norms. Archaeological evidence shows that the entwined development of domestic spaces and human cultural activities was gradual, albeit nonlinear from the Lower Paleolithic through the Upper Paleolithic/later Middle Stone Age. In this process, domestic spaces emerged as common arenas of opportunity for social interaction and knowledge transmission, qualities that may have contributed to and enhanced the development of cumulative culture in Paleolithic society.